Innovationspotenziale des ÖPNVs. Förderung durch Wettbewerb und eine Reform der Finanzierung. - Bölke, Michael (Deutscher Verkehrs-Verlag, 2005)
Der öffentliche Personennahverkehr mit Bussen und Bahnen in Deutschland ist ein unverzichtbarer Bestandteil unserer Mobilitäts- und Alltagskultur. Die Lebensqualität und Urbanität deutscher Städte ist unmittelbar verbunden mit einem attraktiven und leistungsfähigen ÖPNV, insbesondere in den Ballungsräumen. Aber auch in vielen Mittelstädten mit erfolgreichen Stadtbussystemen ist er ein unverzichtbarer Wirtschafts- und Standortfaktor. difu

The quality of life and urbanity in Germany's cities is closely associated with an attractive and efficient local public transport system that makes an important contribution to environmental protection. In this connection, the ÖPNV offers ample opportunities for a new approach to its operational spheres, which is also likely to have a favourable impact on the employment sector. In addition to introducing new technical methods, it will be necessary to reform ÖPNV financing that is aimed more at the transparency and efficiency of the funds used, and by offering incentives to win more travellers for public transport. Also, external costs have to be allocated in a more just way to create balanced conditions for competition among the various means of transport. The imminent ÖPNV liberalization in Germany otters opportunities for more competition by taking into account ambitious and binding environmental and quality service standards. The ÖPNV will thus be in the position of safeguarding and enhancing its role as an environmentally-oriented transport sector. difu
Keywords: Öffentlicher Verkehr; ÖPNV; Bus; Schienenverkehrsmittel; Finanzierung; Wettbewerb; Mobilität; Entwicklungstendenz; Innovation; Zukunft; Verkehrsunternehmen; Umweltschutz; Nachhaltigkeit; Verkehrsleistung; Verkehrsfinanzierung; Beschäftigungspotenzial